The Influence of Pedagogical Values in Paragliding Sports on the Formation of Resilience - Supriyono, Supriyono; Wahyudi, Agung; Paramitha, Sandey Tantra; Asshagab, Muhtar; Ramadhan, Muhammad Gilang (Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to analyse the influence of pedagogical values in paragliding sport on resilience building. Using a mixed-methods approach, the study involved 87 paragliding athletes (64% male, 36% female) with an age range of 18-35 years. Quantitative data was analyzed using Structural Equation Modeling (SEM), while qualitative data was obtained through in-depth interviews with 15 athletes and 5 coaches. The results showed that all five pedagogical values had a significant influence on resilience formation, with emotional control having the strongest influence (β = 0.423, p < 0.001), followed by courage (β = 0.412, p < 0.001), discipline (β = 0.378, p < 0.001), responsibility (β = 0.345, p < 0.001), and cooperation (β = 0.287, p = 0.002). The five values explained 72.4% of the variation in resilience. The Pedagogical Pathway of Paragliding illustrates the gradual process of resilience formation through three phases: Foundation Phase (discipline and responsibility), Development Phase (courage and cooperation), and Integration Phase (emotional control). Qualitative findings revealed that 93% of respondents reported transformative experiences through paragliding that changed the way they perceived challenges, and 87% reported applying the values learned in their life context.